A Fast Method to Estimate the Wall Shear Stress Waveform in Arteries. (February 2013) - Yang, Xin; Hollis, Lyam; Adams, Fiona; Khan, Faisel; Hoskins, Peter R
Introduction: Ultrasound has been applied to measure vessel diameter and blood flow velocity to compute the wall shear rate (WSR) in arteries. This paper describes a fast technique to assess the WSR waveform using an image of a pulsed Doppler waveform downloaded from a modern clinical ultrasound scanner. Methods: A walled vascular phantom has been developed to mimic the physiological condition of brachial arteries, from where measurements were made. A MATLAB program has been developed and used to compute the WSR waveform in a flow phantom from a pulsed Doppler image. The mean WSR obtained from the WSR waveform was compared with the mean WSR derived from the flow rate obtained from a timed collection method. Measurement errors in Doppler velocity estimates from ultrasound scanners were also investigated and used to determine correction factors in WSR calculations. Results: For three different flow phantom depths, 9.5, 14.5 and 19.5 mm, the mean percentage errors between the true and measured WSR were found to be 4.5% (SD = 4.0), 7.4% (SD = 5.1) and 14.2% (SD = 4.1) respectively. Conclusions: The results demonstrated the feasibility of calculating WSR based solely on an image of the Doppler spectrum and arterial diameter measurement, which opens up the possibility of obtaining WSR estimates from generic scanners.